Evaluasi Kualitas Website Program Studi Sistem Informasi Universitas PGRI Madiun Menggunakan Webqual 4.0 - Pamungkas, Ridho; Saifullah, Saifullah (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2019)
This study aims to determine the quality of the website of the Program Studi Sistem Informasi Universitas PGRI Madiun (or later called Prodi SI UNIPMA) with the Webqual 4.0 method which has 4 variables, namely quality of use, quality of information, interaction services and overall quality. The population in this study were students of SI UNIPMA Study Program where 21 respondents were taken as samples. Multiple linear regression analysis is used to test the relationship between variables Webqual 4.0 and student satisfaction. From the results of this study, it can be concluded that the most influential variable in satisfaction is the quality of information with a value of 14.131 and the smallest is the variable quality of use with a value of 2.266. So the recommendations for the website can be obtained is to increase the dimensions of the website's usefulness to students.